Information Processing and Memory in Learning - Didi Nur Jamaludin (Education Mind Based Development Association, 2022)
ABSTRACT The success of learning is strongly influenced by information processing mechanisms and working memory. The characteristics of the initial information will affect the sensory response which is continued by storage in sensory memory. Various stimulus information such as psychophysical stimulus, emotional stimulus, discrepant stimulus and manding stimulus will have an effect on the response back from respondents. Information will be selected to enter short term memory (STM) through a working memory mechanism with the ability to store information within a few seconds. Working memory is managed by the Central executive control center by involving the phonological Loop area, Episode buffer, and Visuo-spatial Sketch Pad. Then the information is continued to Long Term Memory (LTM) with repetition and coding mechanism. Long-term memory storage in the area of ??episodic memory, semantic memory and procedural memory. Working memory is influenced by cognitive load (Cognitive Load) and Cognitive Fit Theory (CFT).